Review of Martín, A. C. Oikonomía. Los orígenes de la reflexión económica en Grecia (2021) - Giglio, Julián (Revista Archai, 2022)
Review of Martín, A. C. Oikonomía. Los orígenes de la reflexión económica en Grecia (2021